Input |
---|

M Y1 (Y2×1×2) |

Result |

2 M Y1 Y2 |

Property as a function |

odd |

Derivative |

d/(dM)(M Y1 (Y2×2)) = 2 Y1 Y2 |

Indefinite integral |

integral 2 M Y1 Y2 dM = M^2 Y1 Y2 + constant |

Skip to content
## M Y1 Y2 X1 X2

## Post navigation

Input |
---|

M Y1 (Y2×1×2) |

Result |

2 M Y1 Y2 |

Property as a function |

odd |

Derivative |

d/(dM)(M Y1 (Y2×2)) = 2 Y1 Y2 |

Indefinite integral |

integral 2 M Y1 Y2 dM = M^2 Y1 Y2 + constant |

The Censes © 2022 | All rights reserved.